Cross-Shore Environmental Gradients in the Western Mediterranean Coast and Their Influence on Nearshore Phytoplankton Communities - Basterretxea, Gotzon; Torres-Serra, Francisco J.; Alacid, Elisabet; Anglès, Sílvia; Camp, Jordi; Ferrera, Isabel; Flo, Eva; Font-Muñoz, Joan S.; Jordi, Antoni; Reñé, Albert; Salgado-Hernanz, Paula M.; Sampedro, Nagore; et al. (Frontiers in Marine Science, 2018)
During summer, when oligotrophic conditions prevail offshore in the Mediterranean Sea, enhanced phytoplankton stripes are often observed in nearshore waters. In this study, we examine the cross-shore hydrographic variability and the associated microbial plankton communities in this zone. Detailed cross-shore underway sampling at 47 coastal sites spread along the Balearic and Catalan coasts revealed the widespread existence of narrow bands of warm and decreased salinity water beholding high phytoplankton biomass (up to 50-fold vs. offshore chlorophyll). Most intense physical and biological anomalies along these transects were generally constrained to the first hundred meters from the shoreline (i.e. a transition zone starting at ̴ 400 m). We use Principal Component Analysis (PCA) and k-means cluster analysis to categorized T, S and Chl in three main types of cross-shore trends. Prevalence of exponential-shaped Chl trends was observed particularly in areas with shoreward directed winds (B1-type). The other two trends (B2 and B3) presented variations off the coast produced by alongshore structures like river plumes, city outfalls and other features. Exponential-shaped cross-shore chlorophyll distribution (B1-type) accumulated 90% of the total transect Chl variation in the first 367±190m from the shoreline, whereas this distance was variable in the other profile types. Repeated daily sampling at one site with this transect typology revealed that wind forcing variations produced fast response on cross-shore T and S properties. Chl was less sensitive to changes at this time-scale. Phytoplankton communities exhibited site-dependent responses to the nearshore environment. Pico- and nanoplankton assemblages, typically dominating coastal assemblages during summer in the Mediterranean Sea, showed lower cross-shore variation. Conversely, larger response to nearshore conditions was observed in microplankton populations. These larger cells, represented by dinoflagellates, cryptophytes and diatoms, were able to actively exploit the nearshore conditions constituting an independent and distinct assemblage from that one prevailing offshore. Our results suggest that despite the importance of local-scale processes in determining biotic structure, some common patterns emerge providing clues on the main drivers of this nearshore niche.